The Influence of Company Size, Leverage, and Profitability on Company Value in the Food and Beverage Industry in the Year Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Asifa Nur Afrida; Basrowi; Rani Sri Sumarsih; Restu Ambiani; Igna Sarova Putriyani N; Saripudin; M Filman Ghaida; Sitti Aminah Arshad; Nur Qamarina Hashan; Ma Jasmine J De Guzman (Southeast Asian Journal of Science and Technology, 2024)
This research aims to analyze the influence of company size, leverage, and profitability on company value in food and beverage sector companies on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The research method uses quantitative methods with secondary data obtained from IDX-published financial reports. The research population involved all food and beverage sector companies listed on the IDX during that period, with samples selected using a purposive sampling method based on certain inclusion criteria. The sample consists of 8 leading companies in the food and beverage sector that meet the requirements. The results of the analysis show that Company Size has a significant negative effect on Company Value, while Leverage has no significant effect. Profitability, on the other hand, has a significant negative influence on Company Value. This finding implies that large assets can have a positive impact on company performance, while non-optimal leverage and profitability management can be detrimental to company value. This study provides an in-depth understanding of the factors that influence company value in the food and beverage industry, as well as providing insight for investors and managers in managing company assets effectively.